1985
DOI: 10.1016/s0376-7388(00)83133-6
|View full text |Cite
|
Sign up to set email alerts
|

On the mechanism of separation of ethanol/water mixtures by pervaporation II. Experimental concentration profiles

Abstract: Ethanol-water concentration profiles in cellulose acetate membranes were measured under steady-state pervaporation conditions. Knowledge of these profiles leads to a better understanding of the diffusion process during pervaporation. The concentration profiles were determined by a film-stack method, using three to six layers. It is shown that permeation of ethanol-water mixtures proceeds in a coupled way and that crossterm diffusion coefficients need to be considered. Furthermore, the occurrence of sorption re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

1987
1987
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 100 publications
(14 citation statements)
references
References 13 publications
0
14
0
Order By: Relevance
“…Actual concentration profiles of pure penetrant in the membrane were reported under steady state pervaporation conditions by several researchers (Kim and Kammermeyer, 1970;Paul and Ebra-Lirna, 1971;Tock et al, 1974;Aptel et al, 1974;Mulder et al, 1985;and Thomas et al, 1989). In the present study experimental binary penetrant profiles are established under steady state pervaporation condition in the membrane by using a stack of symmetric aromatic polyamide membranes.…”
Section: Pervaporation Of Binary Liquid Mixturesmentioning
confidence: 72%
“…Actual concentration profiles of pure penetrant in the membrane were reported under steady state pervaporation conditions by several researchers (Kim and Kammermeyer, 1970;Paul and Ebra-Lirna, 1971;Tock et al, 1974;Aptel et al, 1974;Mulder et al, 1985;and Thomas et al, 1989). In the present study experimental binary penetrant profiles are established under steady state pervaporation condition in the membrane by using a stack of symmetric aromatic polyamide membranes.…”
Section: Pervaporation Of Binary Liquid Mixturesmentioning
confidence: 72%
“…Therefore, we consider both species as a solvent, especially when the molar fraction is close to 0.5. Mulder and Smolders mentioned in their work that excess properties are strongly dependent on concentration and indicated that X 12 can be determined from excess Gibbs energy 26 . Coquelet et al 8 in their work also applied an X 12 dependent on volume fraction ( 1 and  2 ).…”
Section: (15)mentioning
confidence: 99%
“…Many digital models were worked out to determine the diffusion coefficient, from the result of material flow in transitory mode. These models are based on analytical expressions weighted by parameters (Stern & Saxena 1980, Mulder & Smolders 1984, Mulder et al 1985.…”
Section: Introductionmentioning
confidence: 99%